The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1021/ac048315a
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity Ion Mobility Spectrometry/Mass Spectrometry Using Electrodynamic Ion Funnel Interfaces

Abstract: The utility of ion mobility spectrometry (IMS) for separation of mixtures and structural characterization of ions has been demonstrated extensively, including in biological and nanoscience contexts. A major attraction of IMS is its speed, several orders of magnitude greater than that of condensed-phase separations. Nonetheless, IMS combined with mass spectrometry (MS) has remained a niche technique, substantially because of limited sensitivity resulting from ion losses at the IMS-MS junction. We have developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
329
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 246 publications
(336 citation statements)
references
References 64 publications
0
329
0
3
Order By: Relevance
“…29,33 If the width of the ion packets exceeds the inner diameter of the drift tube prior to its arrival at the IMS terminus, then ions are lost and ion transmission efficiency is reduced. The transmission efficiency through the IMS space alone was assumed to be 100% when Tang et al demonstrated near-perfect ion transfer through an ion funnel interface for ESI-IMS-MS. 34 Sysoev el al also concluded ion loss during transmission through IMS tube was minimal when they obtained similar signals with and without a modular IMS inserted between ESI-MS. 35 Gillig et al simulated ion trajectories inside the drift tube and showed that ions were transferred without any loss through the drift tube when they reported an ion focusing guide for MALDI-IMS-MS. 36 However to our knowledge, no direct empirical data has been reported to demonstrate ion transmission is close to 100% in IMS tube.…”
Section: Ion Transmission In Esi-imsmentioning
confidence: 93%
“…29,33 If the width of the ion packets exceeds the inner diameter of the drift tube prior to its arrival at the IMS terminus, then ions are lost and ion transmission efficiency is reduced. The transmission efficiency through the IMS space alone was assumed to be 100% when Tang et al demonstrated near-perfect ion transfer through an ion funnel interface for ESI-IMS-MS. 34 Sysoev el al also concluded ion loss during transmission through IMS tube was minimal when they obtained similar signals with and without a modular IMS inserted between ESI-MS. 35 Gillig et al simulated ion trajectories inside the drift tube and showed that ions were transferred without any loss through the drift tube when they reported an ion focusing guide for MALDI-IMS-MS. 36 However to our knowledge, no direct empirical data has been reported to demonstrate ion transmission is close to 100% in IMS tube.…”
Section: Ion Transmission In Esi-imsmentioning
confidence: 93%
“…26 The timing sequence of the ion mobility experiment was synchronized with the pulsing frequency of the Q-TOF and controlled using a PCI-6711 timing card (National Instruments, Austin, TX).…”
Section: Ion Mobility-quadrupole-time Of Flight Mass Spectrometermentioning
confidence: 99%
“…Improvements to ion transmission through an mobility drift tube were achieved for the continuous mode (i.e., no IMS separation) by combining electrodynamic ion funnels with the IMS drift tube. 26 More recently, our laboratory demonstrated the use of a novel IFT design operated at 1 Torr in combination with a time-of-flight (TOF) mass spectrometer equipped with analog-to-digital converter (ADC) detection. 29 The results showed that improvements in ion packet charge density were accompanied by 10-to 30-fold gains in SNR with respect to signals obtained using the same instrument operating in the continuous mode.…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al have recently reported on ion lossless IMS-MS separations with an IMS drift tube incorporated between two electrodynamic ion funnels. 14 In that experiment, ions were trapped in an "hourglass" ion funnel for 50 to 100 ms at an elevated pressure of 4 torr and then gated into the IMS drift tube in short 50 μs pulses. At the exit of the IMS drift tube, ion packets, spatially dispersed mainly due to thermal diffusion 15 , were captured by a regular ion funnel followed by a short collisional quadrupole.…”
Section: Introductionmentioning
confidence: 99%